(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Verb conjugation is the process of changing the verb according to different forms of tense, person and number. The Russian language has a variety of conjugations that can sometimes seem difficult to learn, especially for beginners.